Advances in affective and pleasurable design proceedings of the AHFE 2018 International Conference on Affective and Pleasurable Design, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA /: proceedings of the AHFE 2018 International Conference on Affective and Pleasurable Design, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA. (c2019) - Unknown
No abstract available